Resettlement of Russians in Tuva in the 1920s–1970s: Ethnodemographic and Ethnoconfessional Aspects - Storozhenko, Alena A. (The New Research of Tuva, 2025)
The article examines the historical conditions and analyzes the main stages of the migration movement of the Russian population into Tuva during the period of the Tuvan People’s Republic and the Soviet era. It analyzes the specific features of the migration situation along the Soviet–Tuvan border during the conditionally “closed” period of the Tuvan People’s Republic and later in the Soviet period, when migration restrictions for Soviet citizens were lifted.Differences are noted in the character, direction, scale, motives, and settlement patterns of Russians in Tuva during the 1920s–1970s, determined both by the policies of the Tuvan government and by the nature of evolving Soviet–Tuvan relations. The study considers the gender and age structure and the composition of Russian migrant families, which developed as a result of these migrations, using as an example the population of the Sizim Village Council of the Kaa-Khem District of the Tuvan ASSR in the broader regional context.The progressive nature of this population group’s development and its considerable demographic potential are revealed. It is established that ethnic and religious factors exerted a significant influence on the motives, forms of migration, and the choice of residence.The main changes in Tuva’s social landscape resulting from Russian migration are identified: the complication of the region’s ethnodemographic structure, the formation of a new sedentary settlement system, the spread of new economic occupations, and the transformation of the sacred landscape.
Keywords: migrations; resettlement; Soviet–Tuvan border; ethnodemographic processes; ethnoconfessional aspect; Tuvan People’s Republic; Tuva; Soviet period; Kaa-Khem District; Tuvans; Russians of Tuva; Old Believers